PENGARUH GAYA KOMUNIKASI PEMIMPIN DAN IKLIM KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PT.RIAU TELEVISI - Indah Azura; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In a formal organization there are elements which are connected to each other. Among others are the element of leadership, communication scene, and work motivation. These element are the sub-system that correspond with one and the other and become support for company as a system with purpose. A leader have a different way and style. The style of leader’s communication must be adjusted with the current organization or company condition and situation, so it can motivate the employee who will be related with the performance improvement and employee’s productivity. Organization communication scene is another important thing, which become a focus attention if they want to promote an institution, because a conducive scene of communication in organization can make the employee to be more motivate in doing their work.This research is titled “The Influence of Leadership Communication Style and Communication Organization Scene to PT. Riau Televisi Employee Performance” The purpose of this research is to find out the leader’s communication style and the communication scene in the organization along with its effect toward the performance of PT. Riau Televisi employees. Theory used is organizational information theory. The method used is explanation research by using questionnaire data as much as 160 employees of PT. Riau Televisi. In this research, because population is relatively small and relatively ease to reach, the author use the total sampling method, also called census. Data analysis in this research is multiple linear analysis using SPSS version 20. The results showed that partial communication style of leadership, known t arithmetic (4.353)> t table (1,975) or Sig. (0,000) <0.05. This means that the leadership style of communication variables significantly affect employee performance. And communication organization scene partially Known t count (6.606)> t table (1,975) or Sig. (0,000) <0.05. This means that the climatic variable of organizational communication has a significant effect on employee performance. And simultaneously Communication style leader and climate communication organization known F count (60,030)> F table (3,054) with Sig. (0,000) <0.05. The meaning is that the communication style of leadership and climatic communication of the organization together have a significant effect on employee performance variable.